Personalized medicine: Function of CFTR variant p.Arg334Trp is rescued by currently available CFTR modulators - Railean, Violeta; Rodrigues, Cláudia S.; Ramalho, Sofia S.; Silva, Iris A. L.; Bartosch, Jan; Farinha, Carlos M.; Pankonien, Ines; Amaral, Margarida D. (Frontiers in Molecular Biosciences, 2023)
Most of the 2,100 CFTR gene variants reported to date are still unknown in terms of their disease liability in Cystic Fibrosis (CF) and their molecular and cellular mechanism that leads to CFTR dysfunction. Since some rare variants may respond to currently approved modulators, characterizing their defect and response to these drugs is essential for effective treatment of people with CF (pwCF) not eligible for the current treatment. Here, we assessed how the rare variant, p.Arg334Trp, impacts on CFTR traffic and function and its response to existing CFTR modulators. To this end, we performed the forskolin-induced swelling (FIS) assay on intestinal organoids from 10 pwCF bearing the p.Arg334Trp variant in one or both alleles of the CFTR gene. In parallel, a novel p.Arg334Trp-CFTR expressing CFBE cell line was generated to characterize the variant individually. Results show that p.Arg334Trp-CFTR does not significantly affect the plasma membrane traffic of CFTR and evidences residual CFTR function. This CFTR variant is rescued by currently available CFTR modulators independently of the variant in the second allele. The study, predicting clinical benefit for CFTR modulators in pwCF with at least one p.Arg334Trp variant, demonstrates the high potential of personalized medicine through theranostics to extend the label of approved drugs for pwCF carrying rare CFTR variants.